6. Isolation, Identification and Sensitivity Test of Staphylococcus aureus on Post Surgery Wound of Local Dogs (Canis familiaris) - Darmawi Darmawi; Amalia Fatma Zahra; M. Nur Salim; Maryulia Dewi; Mahdi Abrar; Syafruddin Syafruddin; Mulyadi Adam (Universitas Syiah Kuala, 2019)
This study aimed to isolate, identify, and sensitivity tested of Staphylococcus aureus from post-surgery wound of local dogs.This study was held in Microbiology Laboratorium of Veterinary Faculty of Syiah Kuala University, Banda Aceh from April to May 2016. The samples were 10 dogs in their 3rd day’s treatment after surgery.The samples were acquired using sterile swab on the wound that was planted on Nutrient Broth (NB), incubated at 37°C for 24 hours, then transferred onto Mannitol Salt Agar (MSA), incubated at 37°C for 24 hours, and after that it was identified with Gram staining, catalase test, sugar test (mannitol and glucose), Metil Red-Voges Proskauer (MR-VP) test and antibiotic sensitivity test. The result of Gram staining showed 7 positive results which identified as coccus formed and coloured as purple. The catalase test showed 7 positive results, the sugar test (mannitol and glucose) showed 4 positive results, the MR-VP showed 4 positive on MR and all negative on VP.. In conclusion, 4 out of 10 samples showed a presence of Staphylococcus aureus on post-surgery wound of local dogs.This bacterium was sensitive on Tetracycline (50%) and also on Streptomycine and Gentamicin (100%). This bacterium resistant to Tetracycline (50%) and Ampicillin (100%).